Institucionalização da gestão democrática da educação como política pública no Sistema Municipal de Ensino de Igarapé-Açu, Pará - PAZ, Vanilson Oliveira (Universidade Federal do Pará, 2017)
This thesis deals with the democratic management institutionalization process of public education at the Municipal System of Education in the municipality of Igarapé-Açu, State of Pará, whose general objective consisted in analyzing how to announce the democratic management of education within the texts law that sustain the Municipal System taught and its effectiveness as a practice management in municipal education over the period 2009-2014, from a qualitative research with case study, with the privileged data sources document analysis and semi-structured interviews with eight individuals involved in the construction process, implementation and evaluation of educational policy in the municipality studied. The study confirmed the hypothesis that the mere creation of the Municipal System of Education and the entire legal apparatus that supports it does not indicate expansion, innovation and installation processes that enable the development and implementation of policies for the democratic management of education pubic locally. Through the effect analysis it was found that the municipality opted for the creation of a Municipal System of Education and the institution of the principle of democratic management through elaborate legal texts collectively; the theme of social and political participation has been highlighted as base aspect of the institutionalization process of democratic management and constituting as a major challenge for the municipal education ensure and expand the local citizenship. Also for understanding the phenomenon of democratic management of education elect some axes that served as the theme for the empirical research (the collective creation, dissemination and knowledge of legal texts, management education to under the body responsible for organizing and managing the Municipal System Teaching, participatory and decentralized management of the City Board of Education, school autonomy with the creation of the election process for school administration and pedagogical proposal of the school and the democratic management in the Municipal Education Plan) demonstrating that the collective construction of texts Legal occurred amid a broad debate and mobilization of local society; education management under the body responsible for organizing and managing the Municipal System of Education is set through a legal framework that historically marks the management of the education system; participatory and decentralized management in the City Board of Education is still long to show how effective practice; promoting school autonomy has its greatest expression in the institution of the election process for school administration and development of the pedagogical proposal of the school, which, however, has not been effective practices in school environments; and, finally, the Municipal Education Plan that has guided the definition, implementation and evaluation of educational teaching policies, resulting in losses for the promotion of quality education at all levels, arrangements and bodies.